Executive Committee Minutes 2016-05-05 - Academic Senate:::::::::
Agenda – Approved. Minutes of 4/21/16 – Approved. Chair Report. President Report. Provost Report. SAC Report. Request to endorse GMC vision statement approved for Senate agenda. Resolution for Senate Chambers approved for Senate agenda. Statewide Senator Report. Vice Chair Report. Vice President of Student Affairs Report. Open Educational Resources Plan – Blessed. Resolution: Calling for Respect for Faculty Authority over Curricular Matters approved for Senate agenda. HSI Report for Senate approved for Senate agenda. Revision to Enrollment in Thesis Courses Policy approved for the Senate agenda. EPC Report. FSAC Report. CFA Report. Senate agenda approved. Appreciation from Chair.